Modeling and controller design for high gain dc-dc converter - P. Soj, Rujay (International Journal of Engineering and Technology, 2019)
This paper presents a mathematical model of a high gain non-isolated dc-dc converter for solar photovoltaic application under closed loop condition. This converter utilizes active switched inductor technology to achieve high gain with reduced voltage stress. All the steady states and transient states are discussed in detail and a suitable PI based voltage mode controller is designed to control the output voltage under various transient conditions. Further the mathematical model is implemented in MATLAB/SIMULINK and performance of the converter is tested.Â